Hubungan Perilaku Ibu dalam Pemilihan Makanan Balita Dengan Statu Gizi Kurang di Wilayah Kerja Puskesmas Wajo - Syastriani Isna Putri Syarif; Asriadi; Anita (Jurnal Syntax Admiration, 2023)
The role of mothers in protecting children's nutritional conditions is by increasing their knowledge, attitudes and actions of mothers regarding toddler nutrition. Nutritional disorders can be caused by a lack of knowledge, attitudes, and actions in an effort to apply information in everyday life.The research method used is descriptive analytical method which means survey research that tries to explore how and why health phenomena occur using 46 samples and 46 populations and found mothers who have good knowledge as much as 11 (23.9%) and less knowledge 35 (76, 1%). while those with good attitudes were 2 (4.3%) and less attitudes were 44 (95.7%) and there were also 17 (37.0%) good and 29 (63.0%) good mothers.So the conclusion of this study is that there is a significant relationship between maternal behavior concerning the knowledge, attitudes and actions of mothers in the dietary selection of children under five under five in the working area of Baubau City Wajo Health Center in 2018, with the hypothesis that HA is treated Hₐ is acceptedSuggestions in this study are to further improve the knowledge of mothers of children under five through the implementation of Posyandu activities and balit weight weighing periodically and continuously and also to improve services through counseling on mothers' knowledge, attitudes, and actions and the selection of food for mothers.